Corporéité et liens affectifs féminins: itinéraire d’un rituel pour Diane Nemorensis et Mater Matuta à Satricum (Gilgameš, 2019)
The religious practices performed in Lazio, for Diane of Nemi, andfor Mater Matuta at Satricum, are well known thanks to literarysources whose details are sufficient to reconstruct them. Theyteach us that these rituals were performed by a group of women toreplay a particular scene in various stages that can be completed orcorroborated by archeology, but they do not necessarily insist onthe importance of their bodies, nor on the emotional ties existingbetween the various devotees. Yet this is one of the foundations ofthe practice, so that the expected result is positively realized. If theyare palpable in one of the two rituals, they are barely mentioned inthe second, which is why they will be the focus of all the attention inthis article.